Stability on coupling SIR epidemic model with vaccination - Helong Liu; Houbao Xu; Jingyuan Yu; Guangtian Zhu (Journal of Applied Mathematics)
We develop a mathematical model for the disease which can be transmitted via vector and through blood transfusion in host population. The host population is structured by the chronological age. We assume that the instantaneous death and infection rates depend on the age. Applying semigroup theory and so forth, we investigate the existence of equilibria. We also discuss local stability of steady states.